Feeding during off-flavour purging in recirculating aquaculture systems? An exploratory characterisation of waterborne and feedborne odour-active compounds in Russian sturgeon (Acipenser gueldenstaedtii) - Egiddi, Matteo; Rodrigues da Silva, Mariana; Ortner, Eva; Debeuf, Bastien; Loos, Helene M.; Buettner, Andrea; Beauchamp, Jonathan (Journal of Agriculture and Food Research, 2026)
Off-flavours are a major challenge in recirculating aquaculture systems (RAS), with geosmin and 2-methylisoborneol (2-MIB) among key contributors to earthy taints. Purging unfed fish in flow-through (FT) water is a standard strategy for off-flavour removal, yet it entails high costs. This descriptive study examined off-flavour development in Russian sturgeon (Acipenser gueldenstaedtii) reared in two systems (RAS and FT depuration) under fed or unfed conditions. Sturgeon fillets, water of both systems, and the commercial feed were analysed via gas chromatography–mass spectrometry/olfactometry (GC–MS/O) combined with aroma extract dilution analysis (AEDA), leading to the identification of 85 odour-active compounds. Water and fillets from RAS showed greater off-odour diversity and potency in terms of their flavour dilution (FD) factors, including geosmin, 2-MIB, 1,3-benzothiazole and pyrazines. In contrast, water and fillets from depuration exhibited fewer off-odours and more desirable notes, such as green , fruity and popcorn-like attributes. The influence of feeding was system-dependent: in depuration, fed animals exhibited lower FD values of key compounds (e.g. , geosmin) but higher odour diversity, including both pleasant (e.g. , mushroom-like, citrus-like) and unpleasant (e.g. , ink-like, sweaty, pungent) notes, whereas in RAS, lower compound diversity and minor odour profile differences were detected in fed sturgeons. Although not statistically relevant, observed differences between groups arose from shifts in relative odour attribute frequencies, compound diversity and FD values across water types and between feeding groups. Overall, sturgeon fed during depuration exhibited a preferable odour profile and a lower geosmin level, but new feedborne odorants were also introduced. The hypotheses generated in this study warrant future targeted sensory assessments and suggest formulation of finishing feeds that can mitigate off-odours and improve the marketability of RAS-reared fish.
CRIS-Team Scopus Importer:2026-01-26
Keywords: Absorption; Depuration; Diet; Feed; Geosmin; Off-odours; RAS